2017
DOI: 10.1037/fam0000271
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from maternal effortful control to child self-regulation: The role of maternal emotional support.

Abstract: This study examined the direct and indirect pathways from maternal effortful control to two aspects of children’s self-regulation – executive functioning and behavioral regulation – via maternal emotional support. Two hundred and seventy eight children and their primary caregivers (96% mothers) participated in laboratory visits when children were 4 and 5 years, and teachers reported on children’s behavior at kindergarten. At the 4-year assessment, maternal effortful control was measured using the Adult Tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…What would be beneficial is not just research on how self-regulation influences eating and weight or what contributes to self-regulation of energy intake, but attention to the developmental course of self-regulation of energy intake over the early years. Zeytinoglu et al [ 178 ] noted that “by 5 years of age, most children demonstrate an increasing capacity for regulating their own arousal, attention, emotional responses, cognitive processes, and goal-oriented behaviors” (p. 170). Advances in child executive functioning in early childhood could initiate a cascade of effects on parenting and contribute to beneficial effects for children [ 86 ].…”
Section: Biology Integrated With Psychosocial Processesmentioning
confidence: 99%
“…What would be beneficial is not just research on how self-regulation influences eating and weight or what contributes to self-regulation of energy intake, but attention to the developmental course of self-regulation of energy intake over the early years. Zeytinoglu et al [ 178 ] noted that “by 5 years of age, most children demonstrate an increasing capacity for regulating their own arousal, attention, emotional responses, cognitive processes, and goal-oriented behaviors” (p. 170). Advances in child executive functioning in early childhood could initiate a cascade of effects on parenting and contribute to beneficial effects for children [ 86 ].…”
Section: Biology Integrated With Psychosocial Processesmentioning
confidence: 99%
“…Although earlier studies largely relied upon cross-sectional designs, longitudinal studies have supported and extended these findings by showing that parenting behavior contributes to the intergenerational transmission of executive functioning (e.g., Cuevas et al, 2014). Likewise, longitudinal findings also demonstrate the effects of maternal effortful control on maternal parenting (e.g., Bridgett, Laake, Gartstein, & Dorn, 2013), and have implicated maternal caregiving behavior in the intergenerational transmission of effortful control (Zeytinoglu, Calkins, Swingler, & Leerkes, 2017). Moreover, experimental animal models support the mostly correlational findings that have appeared in the human literature (e.g., Afonso, Sison, Lovic, & Fleming, 2007;Lovic & Fleming, 2004).…”
mentioning
confidence: 94%
“…One possibility is that mothers who are more emotionally supportive may also exhibit more appropriate IC behavior and strategies themselves that children can model in their own behavior. Support for this idea comes from recent work demonstrating that maternal self‐report of effortful control, defined as a process that enables one to voluntarily shift and focus attention and inhibit or activate a response, predicted observed measures of maternal emotional support during mother–child interaction in the preschool period (Zeytinoglu et al, ). A second possibility is that mothers with greater IC may pass this capacity to their children biologically, as EFs have been identified as among the most heritable psychological traits (Friedman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the development of IC across the preschool period is clearly supported by normative brain development, recent theoretical and empirical work has suggested that developing EF skills are also influenced by the child's caregiving environment (Bernier et al, 2010;Towe-Goodman et al, 2014;Valcan et al, 2017;Zeytinoglu, Calkins, Swingler, & Leerkes, 2017). Given that the development of IC depends heavily on underlying neural development also occurring in the preschool period, one way in which the environment may impact the development of IC abilities is through an influence on neural processes which support them.…”
Section: Influen Ce S Of C Areg Iving B Ehavior On Neur Al De Velopmentioning
confidence: 99%
See 1 more Smart Citation